Mechanism‐Based Fluorogenic trans‐Cyclooctene–Tetrazine Cycloaddition. (27th December 2016) - Vázquez, Arcadio; Dzijak, Rastislav; Dračínský, Martin; Rampmaier, Robert; Siegl, Sebastian J.; Vrabel, Milan
Abstract: The development of fluorogenic reactions which lead to the formation of fluorescent products from two nonfluorescent starting materials is highly desirable, but challenging. Reported herein is a new concept of fluorescent product formation upon the inverse electron‐demand Diels–Alder reaction of 1, 2, 4, 5‐tetrazines with particular trans ‐cyclooctene (TCO) isomers. In sharp contrast to known fluorogenic reagents the presented chemistry leads to the rapid formation of unprecedented fluorescent 1, 4‐dihydropyridazines so that the fluorophore is built directly upon the chemical reaction. Attachment of an extra fluorophore moiety is therefore not needed. The photochemical properties of the resulting dyes can be easily tuned by changing the substitution pattern of the starting 1, 2, 4, 5‐tetrazine. We support the claim with NMR measurements and rationalize the data by computational study. Cell‐labeling experiments were performed to demonstrate the potential of the fluorogenic reaction for bioimaging. Abstract : Per Klick zur Farbe : Ein konzeptionell neuer Ansatz ermöglicht die Synthese von fluoreszierenden 1, 4‐Dihydropyridazinen aus verschiedenen 1, 2, 4, 5‐Tetrazinen mit spezifischen trans ‐Cyclooctenisomeren. Die Systeme wurden zur schnellen fluorogenen Markierung subzellulärer Kompartimente in lebenden Zellen genutzt.